2016
DOI: 10.1155/2016/1468631
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Treatment Outcomes of Retreatment Tuberculosis Patients in Benin

Abstract: Objective. To determine among retreatment tuberculosis patients in Benin baseline characteristics, culture, and drug sensitivity testing (DST) results and treatment outcomes. Materials and Methods. A retrospective national cohort study of all retreatment tuberculosis patients in Benin in 2013 using registers and treatment cards. Results. Of 3957 patients with tuberculosis, 241 (6%) were retreatment cases. Compared to new pulmonary bacteriologically confirmed tuberculosis (NPBCT) patients, there were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
4
4
1
Order By: Relevance
“…This rate was slightly higher than what was observed by Affolabi et al in Benin in 2013 (10%) but was comparable to that of the national drug resistance survey in 2010 [24, 25]. Furthermore, this rate was similar to what was reported by Homolka et al among previously treated cases in Sierra Leone (14.4%) but was lower than 43.7% reported by Dia et al in Senegal [26, 27].…”
Section: Discussionsupporting
confidence: 73%
“…This rate was slightly higher than what was observed by Affolabi et al in Benin in 2013 (10%) but was comparable to that of the national drug resistance survey in 2010 [24, 25]. Furthermore, this rate was similar to what was reported by Homolka et al among previously treated cases in Sierra Leone (14.4%) but was lower than 43.7% reported by Dia et al in Senegal [26, 27].…”
Section: Discussionsupporting
confidence: 73%
“…Patients under 45 years were identified as the target of the disease in our study, eight out of ten. These findings were similar to those found in several studies [12,[18][19]. The predilection of MDR-TB for this more active population mostly drivers in our context, regularly carrying out high promiscuity and the high rate of retreatment failure should worry and lead health authorities and stakeholders involved in fighting TB to set-up new and effective strategies or interventions.…”
Section: Discussionsupporting
confidence: 91%
“…The high incidence of MDR-TB (eight out of ten) found in our study is widely above the literature data [12][13]. This could be attributed to the delay in referring TB clinically suspected cases to TB management services and the mismanagement of patients who are susceptible to anti-TB drugs, knowing that more than half of retreatment TB patients in our study were cases of first-or second-line treatment regimen failure.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…The current findings confirm with other previous studies that retreatment patients are significantly associated to TB disease. The current study findings are slightly high than those documented in Ethiopia (53.8%) [23], on the other hand these findings are markedly high than previous findings in a study conducted in Benin (6%) [24], this difference may be attributed to lack of patient compliance to TB drugs, treatment interruptions due to either (imprisonment, defaulting) and weak active case finding strategies which allow re-infection of the already cured people, HIV prevalence [23]. Further findings of the current study indicated that a high percentage of male patients of age category 20-39 years had TB (14.1%), further the findings were markedly lower than those recorded in Thailand (43.7%) [25].…”
Section: Discussioncontrasting
confidence: 86%